The sounding out project: why pedagogy matters in supporting care-experienced young people - Lio Moscardini; Jesse Paul (Scottish Journal of Residential Child Care)
This paper shares the story of a group of four care experienced young people who participated in an arts project in Aberdeenshire. The research was an evaluative case study which gathered the views and experiences of the young people and the arts educators. The findings showed that by adopting a pedagogical approach to arts education, which was participant-led, a climate of trust and mutual respect was supported. The young people developed a growing sense of their potential as creative individuals and an awareness of possible careers in the creative industries, which previously had not been on their radar.